Fabrication of gelatin–strontium substituted calcium phosphate scaffolds with unidirectional pores for bone tissue engineering - Wu, Yu-Chun; Lin, Wei-Yu; Yang, Chyun-Yu; Lee, Tzer-Min (Journal of materials science. Materials in medicine, 2015)
This study fabricated homogeneous gelatin–strontium substituted calcium phosphate composites via coprecipitation in a gelatin solution. Unidirectional porous scaffolds with an oriented microtubular structure were then manufactured using freeze–drying technology. The resulting structure and pore alignment were determined using scanning electron microscopy. The pore size were in the range of 200–400 μm, which is considered ideal for the engineering of bone tissue. The scaffolds were further characterized using energy dispersive spectroscopy, Fourier transform infrared spectroscopy, and X-ray diffraction. Hydroxyapatite was the main calcium phosphate compound in the scaffolds, with strontium incorporated into the crystal structure. The porosity of the scaffolds decreased with increasing concentration of calcium-phosphate. The compressive strength in the longitudinal direction was two to threefold higher than that observed in the transverse direction. Our results demonstrate that the composite scaffolds degraded by approximately 20 % after 5 weeks. Additionally, in vitro results reveal that the addition of strontium significantly increased human osteoblastic cells proliferation. Scaffolds containing strontium with a Sr-CaP/(gelatin + Sr-CaP) ratio of 50 % provided the most suitable environment for cell proliferation, particularly under dynamic culture conditions. This study demonstrates the considerable potential of composite scaffolds composed of gelatin–strontium-substituted calcium phosphate for applications in bone tissue engineering.